2011
DOI: 10.1007/s12583-011-0160-2
|View full text |Cite
|
Sign up to set email alerts
|

Primary intergranular pores in oolitic shoal reservoir of lower triassic feixianguan formation, Sichuan Basin, Southwest China: Fundamental for reservoir formation and retention diagenesis

Abstract: The Lower Triassic Feixianguan (飞仙关) Formation oolitic shoal reservoir in the Sichuan (四川) basin (Southwest China) is currently an exploration and research highlight in China. The reservoir is widely believed to be formed mainly by burial dissolution and/or dolomitization on the basis of primary intergranular pores. In this study, through a comprehensive geological study on the whole basin, the dissolution and dolomitization are suggested not to be the fundamental factor of reservoir formation and there thus m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 13 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Similar to the outcrops described from the Nanpanjiang Basin, the Feixianguan oolites have been interpreted as representing platform or ramp margin shoals that extend into platform interiors, thinning away from the margin (Ma et al, 2006(Ma et al, , 2007Peng et al, 2010). Although we have not found reference to giant ooids in the Sichuan Basin, petrographic fabrics such as dissolved and collapsed ooids, brittle eggshell compaction of micritic cortices, and alternating cortical laminae of well-preserved micrite and coarse neomorphic spar (figured in Ma et al, 2006;Tan et al, 2011) are identical with those described herein for the Nanpanjiang Basin. Oolite reservoirs in the Sichuan Basin are mostly dolomitized, with much of the reservoir potential from secondary moldic, intercrystalline, vuggy, and fracture porosity, although significant interparticle porosity is also important (Ma et al, 2006;Pan et al, 2010;Peng et al, 2010;Tan et al, 2011).…”
Section: Implications For Hydrocarbon Exploration and Developmentmentioning
confidence: 51%
“…Similar to the outcrops described from the Nanpanjiang Basin, the Feixianguan oolites have been interpreted as representing platform or ramp margin shoals that extend into platform interiors, thinning away from the margin (Ma et al, 2006(Ma et al, , 2007Peng et al, 2010). Although we have not found reference to giant ooids in the Sichuan Basin, petrographic fabrics such as dissolved and collapsed ooids, brittle eggshell compaction of micritic cortices, and alternating cortical laminae of well-preserved micrite and coarse neomorphic spar (figured in Ma et al, 2006;Tan et al, 2011) are identical with those described herein for the Nanpanjiang Basin. Oolite reservoirs in the Sichuan Basin are mostly dolomitized, with much of the reservoir potential from secondary moldic, intercrystalline, vuggy, and fracture porosity, although significant interparticle porosity is also important (Ma et al, 2006;Pan et al, 2010;Peng et al, 2010;Tan et al, 2011).…”
Section: Implications For Hydrocarbon Exploration and Developmentmentioning
confidence: 51%
“…Studies on natural fractures have been ignored [26], leading to incomplete and limited research on related fractures. However, cores from gas fields such as Puguang, Tieshanpo, and Yuanba have shown the widespread distribution of fractures, as well as phenomena of dissolution enlargement and bitumen fillings along fractures [25,28,29]; these findings confirm that fractures serve as significant storage spaces and fluid flow channels in the northeastern Sichuan Basin [30][31][32]. Exploratory studies have demonstrated a close relationship between gas production and the extent of fracture development in northeastern Sichuan [20,31,33].…”
Section: Introductionmentioning
confidence: 93%